The role of NPC1L1 in cancer - Zhang, Renshuai; Zeng, Jun; Liu, Wenjing; Meng, Jingsen; Wang, Chao; Shi, Lingyu; Yang, Shanbo; Chang, Jing; Xing, Dongming (Frontiers in Pharmacology, 2022)
Lipid metabolism showed important roles in the progression of cancer. Many studies have demonstrated that cholesterol played key roles in the progression of tumors, including breast, prostate and colorectal cancers. Niemann-Pick C1-like 1 (NPC1L1), a cholesterol transporter protein that highly expressed in the small intestine and liver, played key roles in the intestinal absorption of cholesterol. Meanwhile, it has been demonstrated that NPC1L1 was directly related to tumorigenesis, development and subduction. NPC1L1 showed potential to become a cancer marker and a new therapeutic target. In this article, we summarized the roles of NPC1L1 in tumorigenesis as well as treatment, and provided references for understanding the relationship between NPC1L1 and tumor.